Funeral procession in front of the Schwarspanierkirche in Vienna - Corvinus, Johann August, 1683-1738 (engraver):::Creator::::::::::::; Kleiner, Salomon, 1703-1761 (artist):::Contributor:::::::::::: (Augsburg; Germany; France; J.A. Pfeffel)
View of a funeral procession in front of the Schwarspanierkirche in Vienna, Austria.